The Dialectic of Philosophical and Literary Exegesis: Mary’s Prophetic Status from the Perspectives of Al-Tabari and Al-Qurthubi - Sulaeman, Mubaidi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This article aims to analyze the dialectic of Qur'anic argumentation regarding Maryam's prophethood from the perspective of two famous commentators, Al-Tabari and Al-Qurthubi, because some interpretations of Maryam's prophethood are considered misogynic by certain circles. Maryam's prophethood is an essential aspect of Islamic theology and has been described in the Qur'an with several verses that provide an overview of Maryam's prophetic role and status. This article aims to understand the interpretive approaches of Al-Tabari and Al-Qurthubi in exploring and explaining Qur'ānic verses related to Maryam's prophethood. The method of analysis used in this article involves a critical review of the commentaries of Al-Tabari and Al-Qurthubi regarding the verses that explain Maryam's prophethood. A comparative approach is used to compare the similarities and differences between the views of the two scholars. In addition, this article also analyzes the historical and cultural context of Al-Tabari and Al-Qurthubi's time to provide a deeper understanding of their interpretations. The analysis shows that Al-Tabari tends to adopt a more historical and linguistic approach in his interpretation. He explores the meanings of words in the relevant verses and relates them to the historical context of the time. On the other hand, Al-Qurthubi tends to adopt a more theological and moral approach in his interpretation. He emphasizes the moral and spiritual messages that can be taken from the prophetic story of Maryam. However, this study has a weak point that can be covered by further research by not exploring the arguments and evidence used by Al-Tabari and Al-Qurthubi in their interpretations critically or by using an approach that can uncover the ideological reasons behind their interpretations.